Lorenzo M. Tañada a centennial birthday tribute to a Filipino hero, 1898-1998. - Tañada, Lorenz ([Manila?] De La Salle University Information Imaging, Inc., 1998)
"This Web-CD is a multimedia compilation of photographs, historical documents & letters, news clippings, rare audio interviews and video clips on Lorenzo M. Tañada one of De La Salle University's most prominent alumni. These materials are currently archived at the De La Salle University Library's Tañada Memorabilia Room."-- CD-ROM back cove
"This Web-CD is a joint project of De La Salle University and Information Imaging, Inc."-- back cover.
Physical description taken from OCLC.
System requirements: Pentium 166 PC; 16 MB RAM; MS Windows 95/98; MS Internet Explorer 3.02+; 8x Multi-session CD-ROM Drive, High Color (16-bit) Display with 800x600 resolutio
Keywords: Tañada, Lorenzo